Women's journey of recovery from sexual assault trauma : a grounded theory - Part 2 - S.E. Duma; J.N. Mekwa; L.D. Denny (AOSIS, 2007)
The purpose of the study was to explore and analyse the journey of recovery which is undertaken by women who have been sexually assaulted, with the aim of discovering the grounded theory of recovery from sexual assault within the first six months following the event of rape. The main research question was: 'What is the journey o f recovery that is undertaken by women within the first six months following sexual assault?' Another question that developed during data collection and data analysis was 'What is the meaning that women attach to recovery?' The findings are discussed under the eight concepts or categories and the context and the intervening conditions that influence the journey of recovery from sexual assault trauma. Refer to part 1 article. These are complemented with abstracts of data from the participants' voices and the related discussions. The developed theory highlights the process and the interconnectedness of the different stages of what the women experience in their journey of recovery from sexual assault trauma.